EFEKTIVITAS METODE PEMBELAJARAN NUMBERED HEAD TOGETHER DALAM MENINGKATKAN KEMAMPUAN BERBICARA BAHASA ARAB DI MI MIFTAHUS SHIBYAN - ilma fahmi aziza (EBTIDA': Jurnal Pendidikan Dasar Islam, 2023)
This study aims to overcome problems in learning Arabic at MI Miftahus Shibyan, especially in understanding the material and lacking speaking skills. The method used is the Numbered Head Together method, which is a cooperative learning method in the group learning model. This method provides opportunities for students to share ideas and consider the most appropriate answer and encourages students to increase the spirit of cooperation. This study used a quantitative approach with a pre-experimental design using one group with pretest and posttest. The research population was class III MI Miftahus Shibyan students, with a sample of 34 students. Data were analyzed using different tests and nonparametric Wilcoxon signed rank test using SPSS software. The results showed a significant increase in students' Arabic skills after using the Numbered Head Together method. This method was effective in improving students' speaking skills, although there were variations in the final results. This study suggests further research to adapt this method to the different needs of students and improve the overall teaching of Arabic. The results of this study also indicate the potential of the Numbered Head Together method in learning other languages ​​and at different grade levels